WICID framework version 1.0: criteria and considerations to guide evidence-informed decision-making on non-pharmacological interventions targeting COVID-19 - Jan M Stratil; Maike Voss; Laura Arnold (BMJ Global Health)
Introduction Public health decision-making requires the balancing of numerous, often conflicting factors. However, participatory, evidence-informed decision-making processes to identify and weigh these factors are often not possible- especially, in the context of the SARS-CoV-2 pandemic. While evidence-to-decision frameworks are not able or intended to replace stakeholder participation, they can serve as a tool to approach relevancy and comprehensiveness of the criteria considered.Objective To develop a decision-making framework adapted to the challenges of decision-making on non-pharmacological interventions to contain the global SARS-CoV-2 pandemic.Methods We employed the ‘best fit’ framework synthesis technique and used the WHO-INTEGRATE framework as a starting point. First, we adapted the framework through brainstorming exercises and application to case studies. Next, we conducted a content analysis of comprehensive strategy documents intended to guide policymakers on the phasing out of applied lockdown measures in Germany. Based on factors and criteria identified in this process, we developed the WICID (WHO-INTEGRATE COVID-19) framework version 1.0.Results Twelve comprehensive strategy documents were analysed. The revised framework consists of 11+1 criteria, supported by 48 aspects, and embraces a complex systems perspective. The criteria cover implications for the health of individuals and populations due to and beyond COVID-19, infringement on liberties and fundamental human rights, acceptability and equity considerations, societal, environmental and economic implications, as well as implementation, resource and feasibility considerations.Discussion The proposed framework will be expanded through a comprehensive document analysis focusing on key stakeholder groups across the society. The WICID framework can be a tool to support comprehensive evidence-informed decision-making processes.